UTILISATION OF VIRTUAL REALITY (VR) AND AUGMENTED REALITY (AR) IN EDUCATION: A COMPREHENSIVE REVIEW - Didi Sudrajat; Fitria Meisarah; Elia Nuriani (Adisam Publisher, 2026)
This research explores the utilisation of Virtual Reality (VR) and Augmented Reality (AR) technologies in education through a comprehensive review. VR and AR technologies offer innovative ways to create immersive and interactive learning experiences, enabling students to better understand complex concepts. The study identifies key benefits of VR and AR in education, including increased student engagement and motivation, as well as the provision of practical, real-life learning environments that are difficult to achieve with traditional methods. However, the study also highlights significant challenges that need to be overcome, such as high costs, technical infrastructure needs, and specialised training requirements for educators. Thus, the conclusions of this study emphasise the importance of careful planning and proper support to maximise the potential of VR and AR as transformational tools in education.